Blue phase liquid crystal: Strategies for phase stabilization and device development - Rahman, M.D.A.; Said, S.M.; Balamurugan, S. (IOP PUBLISHING LTD, TEMPLE CIRCUS, TEMPLE WAY, BRISTOL BS1 6BE, ENGLAND, 2015)
The blue phase liquid crystal (BPLC) is a highly ordered liquid crystal (LC) phase found very close to the LC-isotropic transition. The BPLC has demonstrated potential in next-generation display and photonic technology due to its exceptional properties such as sub-millisecond response time and wide viewing angle. However, BPLC is stable in a very small temperature range (0.5-1 degrees C) and its driving voltage is very high (similar to 100 V). To overcome these challenges recent research has focused on solutions which incorporate polymers or nanoparticles into the blue phase to widen the temperature range from around few degrees C to potentially more than 60 degrees C. In order to reduce the driving voltage, strategies have been attempted by modifying the device structure by introducing protrusion or corrugated electrodes and vertical field switching mechanism has been proposed. In this paper the effectiveness of the proposed solution will be discussed, in order to assess the potential of BPLC in display technology and beyond.